Between Awareness and Resistance: Do Anti-Corruption Education and Deradicalisation Encourage Students to Be Critical? - Al Ayyubi, Ibnu Imam; Nurhikmah; Prayetno, Eko; Apriyanti, Niken Siti Nur; Al-Ghatnaini, Raed Awadh Saeed (CV. Gerasi Insan Nusantara, 2025)
This study aims to analyse the role of anti-corruption and de-radicalisation education in encouraging students to become more critical of social issues. This research methodology uses a qualitative approach with in-depth interview techniques to explore how anti-corruption and de-radicalisation education affects students' critical attitudes. In qualitative research, in-depth interviews also allow researchers to collect rich and detailed data for thorough analysis, which allows them to understand thoroughly, deeply, and contextually the experiences of the interviewees. Participants consisted of 15 students from various majors in higher education who had attended anti-corruption and de-radicalisation education programmes. The selection of participants was purposive to ensure diversity of perspectives. The results showed that anti-corruption and de-radicalisation education significantly increased students' awareness of the negative impact of corruption and the importance of integrity. However, some students also expressed concerns about the lack of transparency and accountability on campus, which may hinder the effectiveness of anti-corruption education. Therefore, this study emphasises the need for a more contextual, participatory and sustainable approach in the implementation of anti-corruption and de-radicalisation education, as well as support from various parties to create a conducive environment for the implementation of integrity values.